Common arterial trunk: pathomorphological changes of unoperated cardiac defect in adulthood - V. I. Hryhoriichuk; Yu. I. Kuzyk; O. I. Boiko (Patologìâ)
Congenital heart defects in adulthood constitute the sufficient proportion of cardiac pathology. The common arterial trunk (CAT) is one of the сongenital cardiac defects that is described in the adult population. Without surgical intervention, patients who survived become inoperable quickly due to the development of early congestive heart insufficiency and pulmonary hypertension.